Formation of in situ VGCFs on carbon fibre felt by chemical vapour infiltration. (1st June 2018) - Yan, Mingyang; Yang, Min; Ren, Musu; Li, Hong; Yu, Mingming; Zhang, Jiabao; Sun, Jinliang
Abstract : In situ vapour grown carbon fibres (VGCFs) were fabricated on carbon felt by chemical vapour infiltration. In this work, the different conditions of the preparation process were determined to obtain VGCFs in large quantities, namely pressure in the reactor and concentration of the aqueous catalyst precursor solution. Observations regarding the growth process of the VGCFs reveal that the catalyst particles with a round shape and diameters of 1 μm or above are most likely to produce VGCFs. The final results indicate that the diameters of VGCFs range from 80 to 150 nm and that their lengths range from 5 to 30 μm. Furthermore, the lengthening and thickening processes of VGCFs were proved to occur simultaneously in the experiment.